Facilitating a Sustainable Electric Vehicle Transition through Consumer Utility Driven Pricing - Valogianni, Konstantina; Ketter, Wolfgang; Zhdanov, Dmitry; Collins, John (International Conference on Information Systems (ICIS), 2018)
A transition to an electrified transportation system is widely assumed to be an important step along the road to environmental sustainability. However, large penetrations of electric vehicles (EVs) may put electricity grids under critical strain, since peaks in electricity demand are likely to increase radically. Efforts to manage demand peaks through pricing schemes may create new peaks at low-price periods, if large numbers of EV owners try to benefit from low prices. We propose a pricing method, called consumer utility driven pricing, which learns from EV owners’ reactions to sub-optimal prices and adjusts announced prices accordingly. We evaluate our results in simulations, where we find that consumer utility driven pricing outperforms current electricity pricing schemes. We test our method in matching both flat and extremely volatile demand profiles and we see that in both cases it performs closely to what it is theoretically possible under perfect information.
Keywords: Electric mobility; Pricing; Green IS; Sustainability; Smart grid stability; 33 Ciencias Tecnológicas; ODS 7 - Energía asequible y no contaminante